La didáctica parvularia y su incidencia en el aprendizaje de los niños y niñas de preparatoria del primer año de educación básica de la escuela de educación básica Jorge Isaac Rovayo, del cantón Baños de Agua Santa, provincia de Tungurahua, período 2013-2014 - Ubilluz Cabrera, Sonia Cristina (2014)
This research work called: Early Childhood TEACHING AND ITS IMPACT ON LEARNING OF CHILDREN FROM SCHOOL FIRST YEAR OF BASIC EDUCATION SCHOOL "JORGE ISAAC Rovayo" CANTON BATHROOMS WATER SANTA, Province TUNGURAHUA, PERIOD 2013 -2014. The general objective was: Develop processes that affect educational preschool learning children First Year High School General Education Basic School "Jorge Isaac Rovayo" Canton Baños de Agua Santa Tungurahua province, period 2013 -2014. The methods used for the preparation of this research work were: the Scientific, Inductive-Deductive method; the techniques used were: Survey applied to teachers in order to determine the incidence of Teaching Preschool in their daily work and observation applied to children through the Learning Test to establish the Learning Development. In the implementation of the survey concluded that teachers: planning activities related to Early Childhood Teaching for week of work in a 57% block, 29% are performed weekly and fortnightly 14%; In addition 57% of respondents almost always develop learning techniques to assimilate new knowledge children, 29% expressed that always and 14% of respondents sometimes develop learning techniques. The Recreation Activities carried out with the kids (as) related to learning by 72% sometimes, 14% almost always and never the same percentage. 86% of the respondents expressed that teachers are always involved with emotion and joy in the activities of the Children's Recreation and 14% of the teachers surveyed almost always argue that their children participate in activities with child emotionality recreation. With children applied test is concluded that: 63% of children have adequate performance if the assimilation of new knowledge and cognitive ability to reach learning and 37% do not have a proper development.